Exploring how external stakeholders shape social innovation in sport for development and peace. Issue 4 (August 2019) - Svensson, Per G.; Hambrick, Marion E.
Highlights: A narrower definition of innovation is adopted with an emphasis on social change. Innovative SDP organizations interact with a range of external stakeholders. Stakeholders are carefully evaluated to ensure a shared commitment to innovation. Social innovation in SDP is a collective process influenced by actors and broader systems. External stakeholders influence innovation at the inter-, intra-, and extra-group levels. Abstract: The purpose of this study was to examine how innovative SDP organizations' interactions with external stakeholders influence the social innovation process. Innovation represents the implementation of new or improved ways to promote social change. The authors conducted semi-structured interviews and focus groups with 48 SDP leaders representing organizations located across six continents. Innovative SDP agencies engaged in numerous non-financial relationships with a strong emphasis on collective learning, a shared willingness to spread the risk of innovation across organizational boundaries, and a reciprocal process for co-creating new and improved solutions for how sport can be used better to promote positive social change. Social innovation in the context of SDP emerged across different levels (intra-, inter-, and extra-group) from a collective and interactive process between SDP organizations and external stakeholders. Their innovation activities included identifying opportunities and generating ideas for implementing new practices and scaling creative solutions. This study extends the existing SDP literature and underscores the need to adopt a more specific external perspective when examining the process of innovation in sport organizations.